Tourist Performing Arts: Balinese Arts-Based Creative Industry - Ni Made Ruastiti (Institut Seni Indonesia Denpasar, 2010)
Creative industry is part of creative economy, which is the implementation of the attempts made to create sustainable development through creativity. Sustainable development refers to a competitive economic climate with renewable resources. Creative economy refers to the fourth stage evolution after agricultural economy, industrial economy and informational economy. As far as the performing arts performed for tourism are concerned, arts seem to develop sustainably. The performing arts such as Cak, Barong and Legong performed for tourism by the Balinese community is the implementation of the local people’s creative industry in developing their artistic life sustainably. They are packaged as the local traditional performing arts.